Experimental study on noise reduction of multi-rotor by phase synchronization. (24th October 2022) - Shao, Mengxue; Lu, Yang; Xu, Xice; Guan, Shujun; Lu, Jiaxin
Highlights: Phase synchronization has an advantage in noise control for multi-rotor aircraft. The co-rotating rotors provide greater noise reduction potential. The method can effectively reduce the noise at low-band and BPF of specific point. The regional noise is reduced by 1–11 dB for co-rotating dual-rotor in experiments. Abstract: Phase synchronization implies that the rotors are synchronized to the same rotation speed and different phases to minimize rotor noise in specific directions. In this study, the influence of phase synchronization on noise directivity and the reducing effect of a multi-rotor were studied experimentally. Based on the multi-rotor noise test platform built in the anechoic chamber, to study the noise control effect of phase synchronization, tests were performed on a small-scale dual-rotor and quadrotor. The influence of phase synchronization on the noise directivity and frequency characteristics was analyzed. Furthermore, the effectiveness of the proposed method was verified using noise-reduction experiments for the target points and regions. The experimental results revealed that: (1) phase synchronization is more advantageous for co-rotating rotors than counter-rotating rotors. Phase synchronization reduces the noise level in all azimuths for the co-rotating rotors, and only a few directions for the counter-rotating rotors. (2) Phase synchronization effectively reduces the sound pressure level in the low-frequency band and multiple harmonic frequencies for a single observation point, especially at the blade-passing frequency. (3) The regional noise is reduced by 1–5 dB and 1–11 dB for the counter-rotating and co-rotating dual-rotor, respectively. Therefore, the experiments show that phase synchronization has a significant advantage in noise control for multi-rotor aircraft.